1997
DOI: 10.1097/00007890-199712270-00035
|View full text |Cite
|
Sign up to set email alerts
|

PREVENTION OF CHRONIC REJECTION IN MOUSE AORTIC ALLOGRAFTS BY COMBINED TREATMENT WITH CTLA4-Ig AND ANTI-CD40 LIGAND MONOCLONAL ANTIBODY1,2

Abstract: Background-In this study, using a murine model of aortic allotransplantation, the role of blockade of signaling through CD28/B7 and CD40/CD40 ligand co-stimulatory pathways in the evolvement of posttransplant vasculopathy was examined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(46 citation statements)
references
References 13 publications
3
42
1
Order By: Relevance
“…The findings of this study are in apparent conflict with several reports that have suggested that CB or CB with donor cells can prevent chronic rejection (5,6,(31)(32)(33). For example, we have previously reported that simultaneous blockade of CD28 and CD40 pathways inhibits the chronic transplant vasculopathy in BALB/c heart grafts in C3H recipients (5), and other groups have demonstrated that blockade of these pathways inhibits transplant vasculopathy in C57BL/10 aortic grafts in C3H recipients (31), rat kidney (32), and heart allograft (33).…”
Section: Dst (contrasting
confidence: 99%
“…The findings of this study are in apparent conflict with several reports that have suggested that CB or CB with donor cells can prevent chronic rejection (5,6,(31)(32)(33). For example, we have previously reported that simultaneous blockade of CD28 and CD40 pathways inhibits the chronic transplant vasculopathy in BALB/c heart grafts in C3H recipients (5), and other groups have demonstrated that blockade of these pathways inhibits transplant vasculopathy in C57BL/10 aortic grafts in C3H recipients (31), rat kidney (32), and heart allograft (33).…”
Section: Dst (contrasting
confidence: 99%
“…The treatment regimen has been different in the various studies, ranging from once at the time of transplantation until continuous administration every 72 hours to prevent chronic rejection in aortic allografts (147). In the latter case, also CD40L effector functions operating within the transplanted graft might be of importance (see 3.4.4).…”
Section: Cd40-cd40l: Role In Transplantationmentioning
confidence: 99%
“…However an absolute requirement for CD28 costimulation for CD154 expression has not been universally reported (39,44). In addition, allograft recipients treated concurrently with CD40-CD154 and CD28-B7 blockade have a greater prolongation of survival than recipients' administration of either agent alone (4,(45)(46)(47). It is therefore likely that CD154 and B7 molecule expression are regulated by independent factors, but there is a degree of interdependence between the two costimulatory pathways.…”
Section: Discussionmentioning
confidence: 99%